Akuntansi Sumberdaya Manusia di Persimpangan Jalan - Irawan Irawan (Politeknik Negeri Lampung, 2016)
This paper is intended to describe the Human Resources Accounting: its recognition, measurement, urgency, implications and development. The method used was literature study approach delivered descriptively. Human resource accounting is accounting for human being as a source of the organization. It is applied aiming at presenting the information, measuring tools and frameworks and their implications in the company. The recognition of HR as a company asset that is based on the ability of HR will provide economic benefits for the company. In recent years, it has significant development which is supported by the determination of the international accounting standards.Â Keywords: Human Resource Accounting ( HRA ), implications , development